Evaluating Household Solid Waste Sampling: Is an Eight-Day Consecutive Method Necessary? A Preliminary Study - Pratama, Mochamad Adhiraga; Wahyuningsih, Ni Putu Sri; Putri, Naila Syafiya (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Household solid waste sampling is a critical part of solid waste management planning, as the results determine the design of the required infrastructure. However, the method suggested by the Indonesian national standard requires time and high costs, as it must be carried out for eight consecutive days. Hence, it is necessary to evaluate this requirement and design a more efficient sampling design without compromising the results. The study conducted solid waste sampling for 16 consecutive days from 31 middle-income households in Jakarta, the Capital City of Indonesia, resulting in a pool of 16 consecutive daily averages of solid waste generation per capita data. From this pool, we generated: (1) solid waste generation per capita from eight consecutive days, (2) six consecutive days, (3) four consecutive days, and (4) eight non-consecutive days data. The results showed that the average of solid waste generation per capita for datasets (1), (2), (3), and (4) are 0.505 (± 0.022) kg/day/cap, 0.495 (± 0.044) kg/day/cap, 0.501 (± 0.035) kg/day/cap, and 0.492 (± 0.02) kg/day/cap consecutively, indicating the same estimates of solid waste generation per capita can be achieved by four scenarios.